Protective effects of the prebiotic on the immunological indicators of rainbow trout (Oncorhynchus mykiss) infected with Aeromonas hydrophila. (July 2016) - Yarahmadi, Peyman; Ghafari Farsani, Hamed; Khazaei, Amin; Khodadadi, Mohammad; Rashidiyan, Ghasem; Jalali, M. Ali
Abstract: The aim of this study was to investigate the protective effects of dietary administration of commercial prebiotic, Immunogen, on immunological indicators, enzymatic responses and stress tolerance in juvenile (81.65 ± 1.49) rainbow trout ( Oncorhynchus mykiss ) following Aeromonas hydrophila infection. The first group of fish was fed with the diet containing 2 g kg −1 Immunogen whilst the control group received the diet free of Immunogen. There were three replicates per group. After 6 weeks feeding, the control group were divided into two treatments injected with saline buffer (control), and 1.5 × 10 8  CFU A. hydrophila respectively. The fish fed with the Immunogen supplemented diet were also injected with 1.5 × 10 8  CFU A . hydrophila . Our results revealed that dietary Immunogen increased the level of white blood cell (WBC) and percentage of lymphocyte ( P  < 0.05), however, the level of red blood cell (RBC), Hematocrit (Hct), hemoglobin (Hb) and percent of monocyte decreased in Untreated-Challenged group but unaffected in the group fed with Immunogen ( P  < 0.05). The level of lysozyme, alternative complement, antiprotease activity, total protein, albumin and globulin decreased in Untreated- Challenged group compared to control group. However, there was an increase in the level of lysozyme, alternative complement, antiprotease activity, bactericidal activity, in the Treated- Challenged group compared to other groups ( P  < 0.05). Serum alkali phosphatase (ALT) and aspartate aminotransferase, significantly increased fallowing challenge with A . hydrophila but in the Treated-Challenged group, there was no significant difference compared to the control group ( P  < 0.05). Lactate dehydrogenase (LDH) level was not different between groups ( P  > 0.05). Serum cortisol and glucose levels were higher in the challenge group, but these levels were lower in fish under challenge that were fed Immunogen-supplemented diet in contrast to the group fed control diet. The stress responses affected by A . hydrophila challenge ( P  < 0.05). Serum sodium, potassium and calcium concentration decreased by A . hydrophila exposure ( P  < 0.05), and Immunogen showed protection effect against this change. Highlights: Administration of 2 g kg −1 Immunogen protect hematological parameters to change against Aeromonas hydrophila infection. Rainbow trout fed 2 g kg −1 Immunogen exhibited higher level of immunological parameters after Aeromonas hydrophila infection. Dietary 2 g kg −1 Immunogen control stress and oxidative response after Aeromonas hydrophila infection.